Histology and morphometry of the testes of adult domestic cats (Felis catus) - Diagone, Karen V. [UNESP]; Feliciano, Marcus A. R. [UNESP]; Pacheco, Marcia R. [UNESP]; Vicente, Wilter R. R. [UNESP] (Sage Publications Ltd, 2012)
Testicles of 30 mongrel cats were analyzed histologically and morphometrically, divided into three groups: G1 (1-2 years old), G2 (over 2 and up to 4 years old) and G3 (over 4 and up to 6 years old). After orchiectomy and histopathology, the morphometric parameters studied were: thickness of the tunica albuginea (72 mu m) and seminiferous epithelium (77.19 mu m), perimeter (53.81; 90.57 mu m), (54.80; 101.07 mu m); area (174.23; 494.55 mu m(2)), (176.68; 629.70 mu m(2)); maximum diameter (14.94; 28.02 mu m), (14.76; 31.66 mu m); minimum diameter (13.25; 21.92 mu m), (13.30; 24.52 mu m); and shape factor (index for regularity of the format) (1.36; 1.36), (1.39; 1.35) of the nucleus and cytoplasm of spermatogonia and Leydig cells, respectively. The results can be used for comparative studies and contribute knowledge concerning the height of the seminiferous epithelium, thickness of the tunica albuginea and size of spermatogonia and Leydig cells.